Mighty justice : the untold story of civil rights trailblazer Dovey Johnson Roundtree - Asim, Jabari, 1962-; Roundtree, Dovey Johnson, 1914-2018; McCabe, Katie (Roaring Brook Press, 2020)
Biography of Dovey Johnson Roundtree, an African American woman who predated Rosa Parks and the Freedom Riders in the civil rights movement in her efforts to join the U.S. Army as one of the first Black women to join its ranks. She would go on to become an attorney in segregated courtrooms in Washington, D.C., and finally as a female minister in the AME church.